Analisis Manajemen Risiko pada UMKM “Warung Teh Nina” Kota Bandung - Nugroho, Kevin Hari; Rusmala, Deviana; Rahmadina, Salsabila; Widyaningsih, Aristanti (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze the implementation of risk management in the UMKM Warung Teh Nina in Bandung using a qualitative descriptive approach. Data were collected through in-depth interviews with the owner and manager to identify the types of risks faced and the mitigation strategies applied. The results reveal that Warung Teh Nina faces various operational, financial, supply chain, and external risks, such as market changes due to campus relocation and the COVID-19 pandemic. Despite these significant risks, the business has managed to survive and grow through effective internal management, structured financial recording, and adaptive marketing and operational strategies. The study concludes that systematic risk management and adaptive capacity are crucial for sustaining UMKM amid dynamic business environments. Keywords: Business Sustainability, Risk Management, Risk Mitigation, UMKM, Warung Teh Nina